2004
DOI: 10.1111/j.1471-4159.2004.02704.x
|View full text |Cite
|
Sign up to set email alerts
|

The 5‐HT2A receptor antagonist M100,907 prevents extracellular glutamate rising in response to NMDA receptor blockade in the mPFC

Abstract: We recently found that intracortical injection of the selective and competitive N-methyl-D-aspartate (NMDA) receptor antagonist 3-(R)-2-carboxypiperazin-4-propyl-1-phosphonic acid (CPP) impaired attentional performance in rats and blockade of 5-hydroxytryptamine (5-HT) 2A receptors antagonized this effect. Here, we used the microdialysis technique in conscious rats to study the effect of CPP on extracellular glutamate (GLU) in the medial prefrontal cortex (mPFC) and the regulation of this effect by 5-HT 2A rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
100
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 96 publications
(233 reference statements)
12
100
0
Order By: Relevance
“…That enhanced glutamate and 5-HT release may not be involved in CPP's effects on perseverative responses is indicated by studies showing that lowering CPP-induced glutamate release by M100907 does not abolish perseverative responding Ceglia et al, 2004; the present results). In addition, reducing but not increasing 5-HT function in the PFC leads to response perseveration in tasks such as reversal learning (Clarke et al, 2004(Clarke et al, , 2005 and in some instances in a 5-CSRT (Winstanley et al, 2004).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…That enhanced glutamate and 5-HT release may not be involved in CPP's effects on perseverative responses is indicated by studies showing that lowering CPP-induced glutamate release by M100907 does not abolish perseverative responding Ceglia et al, 2004; the present results). In addition, reducing but not increasing 5-HT function in the PFC leads to response perseveration in tasks such as reversal learning (Clarke et al, 2004(Clarke et al, , 2005 and in some instances in a 5-CSRT (Winstanley et al, 2004).…”
Section: Discussionsupporting
confidence: 53%
“…Various behavioral deficits induced by NMDA antagonists have been associated with enhanced glutamate release in the mPFC (Moghaddam et al, 1997;Moghaddam and Adams, 1998) and findings in our laboratory indicate that CPP in the mPFC increases glutamate efflux locally and that this was prevented by systemic or intra-mPFC M100907 (Ceglia et al, 2004). Thus, 5-HT 2A receptors in the mPFC play a major role in controlling CPP-induced glutamate release and some aspects of attentional performance in a 5-CSRT task.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Several studies have shown that 5-HT 2A and 5-HT 2C receptors mediate opposing effects on behavioral inhibition, which may relate to their differential effects on dopamine (DA) function (Carli and Samanin, 1992;Koskinen et al, 2000a, b;Ruotsalainen et al, 1997;Passetti et al, 2003;Winstanley et al, 2003Winstanley et al, , 2004Winstanley et al, , 2005. Recent findings also imply a role for 5-HT 2A receptors in regulating glutamate function in PFC , Ceglia et al, 2004.…”
Section: Introductionmentioning
confidence: 87%